Inclusion of Construction Occupational Health and Safety Management System (OHSMS) Components in Building Construction Project - Safira, Sarah; Ramdhan, Doni Hikmat Hikmat (National Journal of Occupational Health and Safety, 2020)
Building construction projects are required to have the Occupational Health and Safety Management System (Sistem Manajemen Kesehatan dan Keselamatan Kerja, OHSMS) due to its high-risk nature. For this purpose, the Ministry of Public Works and People’s Housing of the Republic of Indonesia has issued the Circular Letter Number 66/SE/M/2015 on Costs for Implementing Construction Occupational Health and Safety Management System (OHSMS) in the Field of Public Works. The purpose of this study is to present a detailed description of OHSMS implementation in several building construction projects by using the Ministry’s Circular as the reference. This study is a descriptive study on 30 building construction projects implemented in Indonesia from 2017 to 2019 as the unit of analysis. Data were collected using a questionnaire which was developed based on the content of the Circular of the Minister of Public Works and People’s Housing Number 66/SE/M/2015. This questionnaire was then distributed to respondents using the purposive sampling technic. The OHSMS implementation subcomponents that are most frequently included in the work agreement of building construction projects are work procedure manual development, OHS induction, safety net, protective helmet, worker insurance (BPJS ketenagakerjaan dan kesehatan kerja), OHS expert and/or OHS officer, first aids kit, prohibition sign, and portable fire extinguishers. The least frequently included subcomponents are the provision of worker identity cards (KIP), poster, fall restraint, life jacket, Certificate of OHS Steering Committee (Panitia Pembina Keselamatan dan Kesehatan Kerja, P2K3), medical officer, fogging solution, traffic strip light, OHS flag, and internal audit and inspection programs. A total of 30 building construction projects have implemented OHSMS by including the details of the construction OHSMS implementation, as stated in the Minister of Public Works and People’s Housing Circular Number 66/SE/M/2015 in their work contract.